EFFECT OF WEANING METHODS ON GROWTH, FEED EFFICIENCY AND SOME BEHAVIOURAL TRAITS OF BROWN SWISS CALVES - R. Kocyigit; A. Diler; M. Yanar; O. Guler; R. Aydin; M. Avci (Journal of Animal and Plant Sciences, 2013)
Twenty four Brown Swiss calves were assigned randomly at birth to treatments that evaluated the method of weaning on growth, feed intake, feed efficiency ratio as well as some behavioural traits such as percentage time spent for lying, standing, eating and drinking water. The two experimental treatments were 1) whole milk fed at 8 % of birth weight until abrupt weaning at 49 d of age (AW), 2) whole milk fed at 8% of birth weight until 35 d of age then at 4 % of birth weight until weaning at 49 d of age (GW). Commercial calf starter and dried hay were offered from 4 d of age. Body weights at weaning and 4 months of age were unaffected by the weaning methods. However, body weight gain in the postweaning period was influenced significantly (P<0.05) by the weaning methods and calves in GW group had higher daily weight gain than these in AW group. In the preweaning period, total feed and milk intake of the calves in AWgroup were significantly (P<0.05) greater than those in GW group. In the postweaning period, feed efficiency ratio of the gradually weaned calves was better (P<0.01) than these of calves in AW group. Percentage of time spent for eating feed and drinking water by the calves in GW group were higher (P<0.05) than those in AW group. Overall results of the study suggested that GW method is more appropriate than AW procedure for Brown Swiss calves.
Keywords: Brown Swiss; calves; growth; weaning; behavioural traits